Cash management and corporate profitability: A study of Listed manufacturing firms in Sri Lanka - Thavarasasingam, H.; Anandasayanan, S.; Balagobei, S. (University of Jaffna, 2019)
Cash, the most liquid component of working capital has always being disregarded in financial decision making since it involves investment and financing in short term period. However, it is an important component in firm financial management decision. This study therefore empirically investigates the relationship between cash management and profitability of listed manufacturing companies in Sri Lanka. Cash conversion cycle is used as the measure for cash management while current ratio, debt ratio and sales growth are used as control variables. This study utilized the secondary data whereas Pearson's correlation and multiple regression analysis were used in analyzing the data for the sample of 20 manufacturing companies listed in Colombo Stock Exchange for the period of 2011 to 2017. The results of the empirical finding show that there is a strong negative relationship between cash conversion cycle and profitability of the listed manufacturing companies. It means that as the cash conversion cycle increases it will lead to decreasing profitability of the firms. The study therefore recommends that managers can create a positive value for the shareholders by reducing the cash conversion cycle to a possible minimum level and also accounts receivables should be kept at an optimal level.
Keywords: Cash management; Cash conversion cycle; Profitability